2012
DOI: 10.1126/science.1219518
|View full text |Cite
|
Sign up to set email alerts
|

Meiosis-Specific Noncoding RNA Mediates Robust Pairing of Homologous Chromosomes in Meiosis

Abstract: Pairing and recombination of homologous chromosomes are essential for ensuring reductional segregation in meiosis. However, the mechanisms by which chromosomes recognize their homologous partners are poorly understood. Here, we report that the sme2 gene encodes a meiosis-specific noncoding RNA that mediates homologous recognition in the fission yeast Schizosaccharomyces pombe. The sme2 locus shows robust pairing from early in meiotic prophase. The sme2 RNA transcripts accumulate at their respective gene loci a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
161
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(164 citation statements)
references
References 27 publications
2
161
0
1
Order By: Relevance
“…A recent study in mice reported that a DSB-independent mechanism promotes homolog pairing during premeiotic S phase prior to DSB formation (Boateng et al 2013). The molecular mechanism of DSB-independent homolog recognition remains a mystery, although the aggregation of heterochromatin, noncoding RNA, the SPO11 protein, or sequence-specific DNA-binding proteins such as transcription factors are suggested to contribute to this process (Page and Hawley 2004;Barzel and Kupiec 2008;Dombecki et al 2011;Ding et al 2012;Boateng et al 2013).…”
mentioning
confidence: 99%
“…A recent study in mice reported that a DSB-independent mechanism promotes homolog pairing during premeiotic S phase prior to DSB formation (Boateng et al 2013). The molecular mechanism of DSB-independent homolog recognition remains a mystery, although the aggregation of heterochromatin, noncoding RNA, the SPO11 protein, or sequence-specific DNA-binding proteins such as transcription factors are suggested to contribute to this process (Page and Hawley 2004;Barzel and Kupiec 2008;Dombecki et al 2011;Ding et al 2012;Boateng et al 2013).…”
mentioning
confidence: 99%
“…This process relies on the coordinated action of the long noncoding RNA meiRNA and the protein Mei2 (Watanabe and Yamamoto 1994;Yamamoto 2010). During meiosis, Mei2 is phosphorylated and binds to meiRNA, forming a complex that can efficiently sequester Mmi1 from binding to DSR-containing transcripts, thereby inactivating MTREC-mediated degradation (Watanabe and Yamamoto 1994;Harigaya et al 2006;Ding et al 2012). During vegetative growth, Mmi1 colocalizes with Red1, a core subunit of MTREC.…”
Section: Introductionmentioning
confidence: 99%
“…This 'horse-tail' nuclear movement is essential for promoting homologue pairing [5]. In their live-cell observations of Mei2-GFP, Ding and co-workers noticed that Mei2 dots located at the homologous sme2 loci pair robustly in the early stages of the horse-tail movement, before most other chromo somal loci are paired [1]. When the sme2 locus translocates to another chromosomal site, the robust pairing mechanism also transfers to this new site.…”
mentioning
confidence: 99%
“…When the sme2 locus translocates to another chromosomal site, the robust pairing mechanism also transfers to this new site. Inactivation of the promoter in only one sme2 locus of a pair of homologues impairs the robust pairing, suggesting that the transcribed meiRNAs must be tethered to homologous loci for pairing [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation